PENGARUH PENERAPAN COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IIS SMAN 14 PADANG TAHUN PELAJARAN 2014/2015 - Fadillah, Dini - (Pendidikan Matematika, 2014)
This research is background by the comprehending of students mathematic concept is still low. And the students do not have the braveness to give share their idea. The aim of this research to see while Cooperative Learning Tipe Two stay Two Stray has significant effect to comprehend the students mathematic concept . The type of this research is experimental research by using pre test and post test group. The population of students of second grade of social senior high school of 14 Padang. The instrument used in this research is comprehending students concept in essay test with the reliability 0,79. Based on the calculating of t-test is found ttest = 4.41 , it shows that it is bigger than ð¡0,025=2,04 . it show that the hypothesis is accepted. So that there is significant effect by using Cooperative Learning Type Two stay Two Stray in students mathematic concept comprehending for the second grade of social concentration senior high school of 14 Padang .